TIF1 Activates the Intra-S-Phase Checkpoint Response in the Diploid Micronucleus and Amitotic Polyploid Macronucleus of Tetrahymena - Yakisich, J. Sebastian (The American Society for Cell Biology, 2006)
The ribosomal DNA origin binding protein Tif1p regulates the timing of rDNA replication and is required globally for proper S-phase progression and division of the Tetrahymena thermophila macronucleus. Here, we show that Tif1p safeguards chromosomes from DNA damage in the mitotic micronucleus and amitotic macronucleus. TIF1p localization is dynamically regulated as it moves into the micro- and macronucleus during the respective S phases. TIF1 disruption mutants are hypersensitive to hydroxyurea and methylmethanesulfonate, inducers of DNA damage and intra-S-phase checkpoint arrest in all examined eukaryotes. TIF1 mutants incur double-strand breaks in the absence of exogenous genotoxic stress, destabilizing all five micronuclear chromosomes. Wild-type Tetrahymena elicits an intra-S-phase checkpoint response that is induced by hydroxyurea and suppressed by caffeine, an inhibitor of the apical checkpoint kinase ATR/MEC1. In contrast, hydroxyurea-challenged TIF1 mutants fail to arrest in S phase or exhibit caffeine-sensitive Rad51 overexpression, indicating the involvement of TIF1 in checkpoint activation. Although aberrant micro- and macronuclear division occurs in TIF1 mutants and caffeine-treated wild-type cells, TIF1p bears no similarity to ATR or its substrates. We propose that TIF1 and ATR function in the same epistatic pathway to regulate checkpoint responses in the diploid mitotic micronucleus and polyploid amitotic macronucleus.